Identification of Novel Alleles and Structural Haplotypes of Major Histocompatibility Complex Class I and DRB Genes in Domestic Cat (Felis catus) by a Newly Developed NGS-Based Genotyping Method - Okano, Masaharu; Miyamae, Jiro; Suzuki, Shingo; Nishiya, Kohei; Katakura, Fumihiko; Kulski, Jerzy K.; Moritomo, Tadaaki; Shiina, Takashi (Frontiers in Genetics, 2020)
The major histocompatibility complex (MHC) is a highly polymorphic and duplicated genomic region that encodes transplantation and immune regulatory molecules. Although it is well-known that particular MHC allelic polymorphisms and haplotypes are genetically relate to immune-mediated diseases detailed information of the cat MHC (Feline Leukocyte Antigen; FLA) genetic and haplotypic structure and diversity is limited in comparison to humans and many other species. In this study, to better understand the degree and types of allele and allelic haplotype diversity of FLA-class I (FLA-I) and FLA-DRB loci in domestic cats, we identified six expressible FLA-I loci in peripheral white blood cells by in silico estimation of the coding exons and NGS-based amplicon sequencing using five unrelated cats. We then used a newly developed NGS-based genotyping method to genotype and annotate 32 FLA-I and 16 FLA-DRB sequences in two families of 20 domestic cats. A total of 14 FLA-I and seven FLA-DRB were identified as novel polymorphic sequences. Phylogenetic analyses grouped the sequences into six FLA-I (FLA-E/H/K, FLA-A, FLA-J, FLA-L, FLA-O and a tentatively named FLA-E/H/K_Rec) and four FLA-DRB (FLA-DRB1, FLA-DRB3, FLA-DRB4 and FLA-DRB5) lineages. Pedigree analysis of two cat families revealed eight distinct FLA structural haplotypes (Class I - DRB) with five to eight FLA-I and two to three FLA-DRB transcribed loci per haplotype. It is evident that the eight FLA haplotypes were generated by gene duplications and deletions, and rearrangements by genetic recombination with the accumulation and/or inheritance of novel polymorphisms. These findings are useful for further genetic diversity analysis and disease association studies among cat breeds and in veterinary medicine.